Polymorphic low-grade neuroepithelial tumors of the young: disease characteristics and treatment decisions from the epilepsy surgery perspective - Guilu He; Guilu He; Hongping Tan; Shaochun Li; Limin Zhang; Qiao Li; Hainan Li; Yanwu Guo; Qiang Guo (Frontiers in Neurology)
BackgroundThe Polymorphic Low-Grade Neuroepithelial Tumor of the Young (PLNTY) is a rare, epilepsy-associated brain tumor that has been increasingly recognized but is not well understood due to the scarcity of clinical reports. Our study reviews the clinical characteristics and treatment outcomes of 14 patients with PLNTY to enhance the understanding of this condition from an epilepsy surgery perspective.MethodsWe performed a retrospective analysis of 14 PLNTY cases at our hospital. A literature review on prior studies was also conducted.ResultsOur study included 8 males and 6 females, all presenting with epilepsy. Despite anti-seizure medication, 92.3% of patients continued to have seizures, with 58.3% diagnosed as having drug-resistant epilepsy. Neuroimaging revealed that 64.3% of the lesions were in the temporal lobe, with 75.0% showing calcification on CT, 71.4% exhibiting mixed signals on T2-weighted images, and 92.7% showing tumor enhancement. The transmantle sign was noted in 57.1% of T2 FLAIR sequences. EEGs indicated abnormal activity in 69.2% of patients, with 30.7% showing bilateral discharges. SEEG in two patients confirmed the tumor’s epileptogenicity. A 78.6% total resection rate was achieved, with a 90.0% postoperative seizure-free rate and an 85.7% excellent Engel grade 1 rate. No instances co-occurring with focal cortical dysplasia (FCD) were observed.ConclusionPLNTY is characterized by unique neuroimaging features and a strong association with epilepsy. SEEG is pivotal for cases with unclear lateralization, aiding in identifying the link between the tumor and seizures. Following established epilepsy surgery protocols for brain tumor management, early intervention and extended resection can improve the rate of postoperative seizure freedom.